Pengaruh Asupan Zat Gizi Harian dan Jogging Terhadap Perubahan Berat Badan pada Remaja Overweight di Surakarta - Muharramah, Alifiyanti; Doewes, Muchsin; Tamtomo, Didik Gunawan (Wellness And Healthy Magazine, 2019)
Overweight is an unbalanced nutritional status due to excessive nutritional intake resulting in an energy imbalance that can cause health problems. More nutrients that arise in adolescence tend to continue into adulthood and the elderly. Nutritional status in adolescents can indicate the level of nutritional problems that occur, namely problems regarding daily intake in adolescents. Fulfillment of daily care in adolescents impacts on body weight so it needs to be considered related to the expenditure of energy required, one form that can be done can be in the form of physical training in the form of aerobic exercise such as jogging. Jogging is included in cardio or aerobic exercise which has the benefit of increasing fitness and burning fat in the process of weight loss. This research is a type of analytic research with quasi experimental design with a pre-post test control group design. This research was conducted in the presence of a treatment group and a control group. This research was conducted for 12 weeks, namely in August-September 2017. Based on statistical tests conducted using the One Way Anova test with Post Hoc Games - Howell, showed that in the treatment group that is the regulation of daily nutrient intake (carbohydrates, fats, fiber) with jogging compared to the control group ie breakfast consumption in students without jogging exercises can affect changes in body weight that is indicated by a decrease in body weight in students, this can be seen from the value of p 0.032 which indicates a significant change in weight loss in students.The effect of the breakfast consumption control group with the treatment group daily intake of food and jogging on weight loss in overweight adolescents.